Antifungal potential of Leptadenia Hastata against some pathogenic fungi - Umaru, Isaac John; Fasihuddin, bin Badruddin Ahmad; Wakawa, Henry Y.; Umaru, Hauwa A.; Umaru, Kerenhappuch I. (Science Publications, 2018)
The objective of this study was to evaluate if the plant extract could provide antifungal potential against some pathogenic fungi. Extract of Dichloromethane solvents was used for disc diffusion assay. The inhibitory concentration of the extract was performed by broth dilution method and zone of inhibition was studied by disc diffusion method at the concentration of 25, 50, 100, 250, 500 and 1000ppm in DMSO. Fluconazole was used as the reference control for antifungal study. The extract showed maximum inhibition potential of zone of inhibition against most of the pathogen (Aspergillus niger, Aspergillus flavus, Candida tropicalis and Fusarium oxysporium) used at concentration 25ppm to 250ppm with zone of inhibition (3.45±0, 3.33±0.12, 3.07±0.05 and 2.97±0.10mm respectively). The extract showed minimum inhibition potential against Fusarium oxysporium in all the concentration when compared with the control as well as to the other pathogens. Aspergillus niger and Aspergillus flavus was found to be more sensitive to Dichloromethane leaf extract followed by Candida tropical and lastly fusarium oxyspurium. The Present study indicates the potential usefulness of Dichloromethane leaf extract of Leptadenia hastata as antifungal agent. © 2018 Isaac John Umaru, Fasihuddin A. Badruddin, Henry Y. Wakawa, Hauwa A. Umaru and Kerenhappuch I Umaru.